PHYSICOCHEMICAL STUDIES OF SOME TRIVALENT METAL β-DIKETONATES (1976)
Forty trivalent metal chelates of 2-thenoylacetone,2 thenoyltrifluoroacetone, 2-furoylacetone, 2-furoyltrifluoroacetone. benzoylacetone, benzoyltrifluoroacetone and nicotinoyltrifluoro— acetone (where metal(Hl) = Al, Crf Mn, Fe and Co) as well as some mixed ligand p-diketonate complexes of iron(IH), have been prepared and their spectroscopic and magnetic properties have been examined. Among the series of compounds studied, Al(fbd) Mn(fbd)3, AKtftbd), Co(tftbd)3, Cr(tffbd)3, Mn(tffbd)3, Co(tffbd)3, M(tbd)3, M(tfpybd)3 (where M = Al, Cr, Mn, Fe and Co ), Fe(bzac)2 (tftbd), Fe(tftbd)2(bzac), Fe(fbd)2(tbd)and Fe(tbd)2(fbd) have been investigated for the first time. The effects of 3-pyridyl, 2-thienyl, 2-furyl, phenyl and trifluoromethyl substituents have been discussed in relation to the lowest spin-allowed transition, п3- п4 and M-O,VC--O and VC--C-—C stretching vibrations. Substitution of a methyl group in 2,4-pentanedione - by a furyl ring, and a methyl group in 1-(2-furyl )-l,3-butanedione by a trifluoromethyl are found to strengthen the C---O and C —C—C and weaken the M—0 bonds of the chelate rings; while the 2-thienyl group shifts the M—O and C -- 0 to lower, and C---C to higher frequencies. The phenyl substituent, as expected, strengthens the M-O and C---C bonds and weakens the C--O bonds. The most sensitive M-0 stretching modes follow the order Co(lII) >A1(III) > Cr(III)> Mn (III) > Fe (III). However, the lowest spin-1llowed п3- п4 translation of the β-ketoenolate anion, although found to be metal sensitive, does not follow the same trend. Trifluoromethyl group substitution resulted in the bathochromic shift of the п3- п4 transitions. The ligand field energy parameters Dq,f (ligand)), B35 and β35 have been calculated and the following order of nephelauxetic effect in the ligands has been derived: Htffbd > Htbd > Hfbd > Hacac > Hbztfac > Htftbd > Hbzac > Htfpybd. While the spectrochemical series of the ligands depicted by the magnitude of f(ligand) parameter also follow:'.the orders tfpybd < bztfac < fbd < tffbd < tbd < acac ~ bzac < tftbd. The reflectance spectra and magnetic properties of these compounds revealed that they are very similar to the corresponding tris—(2,4—pentanedionato) metal(III) octahedral complexes.